Aprendizaje colaborativo en entornos virtuales: los recursos de la Web 2.0 - Quesada Pacheco, Allen (2013)
This paper describes the meaning and importance of Web 2.0 tools in virtual learning environments as essential resources for meaningful and collaborative eLearning. The article also synthesizes the importance of the collaborative tools of the Web 2.0 for asynchronous and synchronous communication. Similarly, a detailed description of the characteristics of virtual environments and the Web 2.0 tools is provided, which include:  1) communication tools, 2) management and organizational learning tools, 3) knowledge creation tools, and 4) tools for sharing resources. An appraisal of these tools is developed for internet-based learning at the university level.